A time-evolution model for the privacy degree of information disseminated in online social networks. (1st January 2013) - Othmane, Lotfi ben; Weffers, Harold; Angin, Pelin; Bhargava, Bharat
People tend to share private information with their friends on online social networks (OSNs). The common position is that the shared information eventually reaches all users of the network since OSNs exhibit the small-world property. However, dissemination of private information in an OSN exhibits a set of factors that need to be accounted for in order to create more realistic models of the evolution of the privacy degree of information disseminated in an OSN. Among these factors are relationship strength between communicating users, influence of neighbours (i.e., friends), users' adoption of new information, change of information, and dynamics of the structure of OSNs. This paper proposes a time series model for measuring the privacy of information disseminated in an OSN using the factors listed above. It shows through simulating the dissemination of private information in an OSN that the privacy of information does not vanish, but in most cases declines to a saturation level related to the information dissemination factors. The results also show how likely a user can get the information when the factors are accounted for.